Discovery of a chlorophyll binding protein complex involved in the early steps of photosystem II assembly in Synechocystis - Knoppová, Jana; Sobotka, Roman; Tichy, Martin; Yu, Jianfeng; Konik, Peter; Halada, Petr; Nixon, Peter J; Komenda, Josef (The Plant cell, 2014)
Efficient assembly and repair of the oxygen-evolving photosystem II (PSII) complex is vital for maintaining photosynthetic activity in plants, algae, and cyanobacteria. How chlorophyll is delivered to PSII during assembly and how vulnerable assembly complexes are protected from photodamage are unknown. Here, we identify a chlorophyll and β-carotene binding protein complex in the cyanobacterium Synechocystis PCC 6803 important for formation of the D1/D2 reaction center assembly complex. It is composed of putative short-chain dehydrogenase/reductase Ycf39, encoded by the slr0399 gene, and two members of the high-light-inducible protein (Hlip) family, HliC and HliD, which are small membrane proteins related to the light-harvesting chlorophyll binding complexes found in plants. Perturbed chlorophyll recycling in a Ycf39-null mutant and copurification of chlorophyll synthase and unassembled D1 with the Ycf39-Hlip complex indicate a role in the delivery of chlorophyll to newly synthesized D1. Sequence similarities suggest the presence of a related complex in chloroplasts.
Keywords: Chlorophyll Binding Proteins; Synechocystis; proteiny vázající chlorofyl; fotosystém II (proteinový komplex); spektrometrie hmotnostní - ionizace laserem za účasti matrice; Photosystem II Protein Complex; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization